二十一世纪中国文化产业 ：的趋势与对策 = China's cultural industries in 21st century - 聂 瑞平 Nie, Rui Ping (2008)
Steadfast in its stand on Marxist dialectical materialism and historical materialism viewpoint and methodology, the thesis applies the basic principles of sociology and economics theories, by combining pure research and applied research, proposes and situation and problem analysis of China's cultural industry in the face of transition, complexity and growth.